2016
DOI: 10.1007/s13178-016-0242-0
|View full text |Cite
|
Sign up to set email alerts
|

College Students, Sexualities Identities, and Participation in Political Marches

Abstract: Student protest is often an engine of social change for sexual minorities and other oppressed groups. Through an analysis of college students in the Add Health survey (n = 2, 534), we found that sexual minorities attend more political marches than heterosexuals. To understand why this sexuality difference occurs, we performed a logistic regression analysis to decipher the importance of four explanations: essentialism, selection, embeddedness, and conversion. We discovered that participation in political groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 71 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Another possible mechanism is what Egan () calls conversion , wherein the process of “coming out” or publicly disclosing one's LGB sexual identity facilitates one's growing awareness of their oppressed status and rejection of internalized heteronormative values (Swank and Fahs , ). Related to this form of consciousness raising, the underdog thesis suggests that members of oppressed groups are more aware of inequality and supportive of policies to eliminate it than are dominant group members (Robinson ; Robinson and Bell ).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible mechanism is what Egan () calls conversion , wherein the process of “coming out” or publicly disclosing one's LGB sexual identity facilitates one's growing awareness of their oppressed status and rejection of internalized heteronormative values (Swank and Fahs , ). Related to this form of consciousness raising, the underdog thesis suggests that members of oppressed groups are more aware of inequality and supportive of policies to eliminate it than are dominant group members (Robinson ; Robinson and Bell ).…”
Section: Introductionmentioning
confidence: 99%
“…LGB-identified voters also tend to show more liberal preferences on issues beyond those having to do specifically with LGBT rights, including foreign policy, environmental issues and the role of government (Egan et al, 2008;Egan and Sherrill, 2006). And echoing the finding about Black students in the NSLVE study cited above, Eric Swank and Breanne Fahs (2016) found that college students who identified as LGBT were twice as likely as their straight counterparts to engage in protest. These differences were particularly pronounced among LGB respondents who rejected other forms of social hierarchy and who were members of other marginalized groups as well (Swank and Fahs, 2016).…”
Section: The Political Distinctiveness Of Lgbt Peoplementioning
confidence: 76%
“…More recent data has made it possible to explore more traditional measures of LGBT political attitudes and behavior (Egan 2012; Egan et al, 2008; Swank and Fahs 2016, 2013). Pat Egan and his colleagues (2008), for example, found that lesbian, gay and bisexual (LGB) people are overwhelmingly likely to identify as and to vote for Democrats and also that they profess a greater sense of civic duty than their straight counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although climate change perceptions are not inherently political, the mass politicization of this issue and consistent connection to party politics in the US makes it likely that LGBTQ+ political culture helps shape views. There have been few direct examinations of LGBTQ+ political culture, but research has demonstrated increased engagement in both insider and outsider political tactics like voting (Bowers and Whitley 2021; Strode and Flores 2021; Swank and Fahs 2017, 2019) and protest (Bowers and Whitley 2021; Swank and Fahs 2017, 2019). To explain these outcomes and why we are likely to see increased political engagement among LGBTQ+ populations, scholars point to three theoretical explanations: sociodemographics not related to LGBTQ+ identity; shared LGBTQ+ identities; and shared oppression.…”
Section: Background and Theorymentioning
confidence: 99%